An Enhanced Load-Transfer Model for Pile-Supported Embankments Incorporating Slip Between Pile and Soil - Chengfu Zhang; Yongjie Tan; Chaoguang Huang; Yufei Liu; Shao Yue; Gaoqiao Wu (Buildings)
The primary objective of this study is to establish an innovative theoretical framework for analyzing the behavior of an end-bearing pile-supported embankment. This proposed methodology extensively investigates various aspects, including the characteristics of relative slip at the interface between the pile and soil, the distinctive non-uniform deformation patterns typically observed in soft soils, and the substantial influence of pile–soil interaction on the evolution of soil arching phenomena. To precisely capture the frictional relationship and relative displacement within the pile–soil system, we introduce an enhanced ideal elastic-plastic model. Additionally, a deformation function is incorporated to simulate the non-uniform deformation of soft soils, and an improved soil arching model is developed to assess its impact on the overall behavior. The analytical solution is derived through the implementation of a stress and volume deformation continuity condition, and its validity is effectively demonstrated through numerical simulations. The results indicate that under the load of the embankment, relative slip at the pile–soil contact surface is a significant phenomenon and should not be neglected in theoretical calculations. The relative displacement between the pile and soil initially exhibits a linear relationship with depth, and later follows a quadratic function as depth increases.